Large-eddy simulation of flow over a cylinder with Re_D from 3.9× 10^3 to 8.5× 10^5: a skin-friction perspective. (5th May 2017) - Cheng, W.; Pullin, D. I.; Samtaney, R.; Zhang, W.; Gao, W.
Abstract : We present wall-resolved large-eddy simulations (LES) of flow over a smooth-wall circular cylinder up to Re_D=8.5× 10^5, where Re_D is Reynolds number based on the cylinder diameter D and the free-stream speed U_∞ . The stretched-vortex subgrid-scale (SGS) model is used in the entire simulation domain. For the sub-critical regime, six cases are implemented with 3.9× 10^3Re_D10^5 . Results are compared with experimental data for both the wall-pressure-coefficient distribution on the cylinder surface, which dominates the drag coefficient, and the skin-friction coefficient, which clearly correlates with the separation behaviour. In the super-critical regime, LES for three values of Re_D are carried out at different resolutions. The drag-crisis phenomenon is well captured. For lower resolution, numerical discretization fluctuations are sufficient to stimulate transition, while for higher resolution, an applied boundary-layer perturbation is found to be necessary to stimulate transition. Large-eddy simulation results at Re_D=8.5× 10^5, with a mesh of 8192× 1024× 256, agree well with the classic experimental measurements of Achenbach ( J. Fluid Mech., vol. 34, 1968, pp. 625–639) especially for the skin-friction coefficient, where a spike is produced by the laminar–turbulent transition on the top of a prior separation bubble. We document the properties of the attached-flow boundary layer on the cylinder surface as these vary with Re_D . Within the separated portion of the flow, mean-flow separation–reattachment bubbles are observed at some values of Re_D, with separation characteristics that are consistent with experimental observations. Time sequences of instantaneous surface portraits of vector skin-friction trajectory fields indicate that the unsteady counterpart of a mean-flow separation–reattachment bubble corresponds to the formation of local flow-reattachment cells, visible as coherent bundles of diverging surface streamlines.